Youth volunteerism – journey towards a "Better Singapore" - Tan, Yvonne (2018)
This research aims to investigate the phenomena of youth volunteerism in Singapore. By applying the concept on governmentality, the paper seeks to offer insights on the trends on youth volunteerism in Singapore. The paper seeks to examine the successes of the model adopted by Singapore to promote youth volunteerism by examining both the macro levels – dominant state mechanism, and the micro-level negotiations of the youths as they take on the responsibility to care for the community in this system. Through qualitative interviews conducted with youths, I provide deep insights on youth’s attitudes towards mandatory volunteering policies and their motivations to volunteer with the community.